The Use of Molecular Simulation-Assisted Discovery Learning in Improving Science Process Skills - Tania, Lisa; Saputra, Andrian; Sari, Mutiara (Jurnal Pendidikan Progresif, 2020)
The Use of Molecular Simulation-Assisted Discovery Learning in Improving Science Process Skills. Objectives: This study aimed to describe the effectiveness of molecular simulationassisted discovery learning (MSADL) in improving science process skills (SPS) on chemical equilibrium. Methods: This research used the matching-only pretest-postest control group design. The population in this study was all students of XI MIA at MAN 1 Bandar Lampung in 2019/ 2020. The sample was XI MIA 5 and XI MIA 6 obtained by purposive sampling. The data analysis technique used the t-test. Findings: The results showed the average n-gain of students’ SPS using MSADL was 0.76 in high criteria, while the average n-gain of students’ SPS using conventional learning was 0.54 in moderate criteria. The t-test results showed that the average n-gain of students’ SPS using MSADL was higher than students’ SPS using conventional learning. Conclusion: It can be concluded that MSADL is effective in improving students’ SPS on chemical equilibrium. Keywords: discovery learning, science process skills, chemical equilibrium. DOI: http://dx.doi.org/10.23960/jpp.v10.i3.202012